"Don't judge me!": Links between in vivo attention bias toward a potentially critical judge and fronto-amygdala functional connectivity during rejection in adolescent girls. (June 2021) - Sequeira, Stefanie L.; Rosen, Dana K.; Silk, Jennifer S.; Hutchinson, Emily; Allen, Kristy Benoit; Jones, Neil P.; Price, Rebecca B.; Ladouceur, Cecile D.
Highlights: We used innovative, ecologically valid eye-tracking and fMRI measures to examine social threat sensitivity in adolescent girls. Findings support the reliability of a novel in vivo attention bias task. Real-world attentional biases toward social threat correlated with amygdala-anterior PFC functional connectivity during social evaluation. Greater positive amygdala-anterior PFC connectivity during social evaluation could suggest disrupted prefrontal regulation of the amygdala. Disrupted prefrontal regulation of the amygdala could contribute to deployment of attention to social evaluative threat in daily life. Abstract: During adolescence, increases in social sensitivity, such as heightened attentional processing of social feedback, may be supported by developmental changes in neural circuitry involved in emotion regulation and cognitive control, including fronto-amygdala circuitry. Less negative fronto-amygdala circuitry during social threat processing may contribute to heightened attention to social threat in the environment. However, "real-world" implications of altered fronto-amygdala circuitry remain largely unknown. In this study, we used multiple novel methods, including an in vivo attention bias task implemented using mobile eye-tracking glasses and socially interactive fMRI task, to examine how functional connectivity between the amygdala and prefrontal cortex (PFC) during rejection and acceptance feedback from peers is associated with heightened attention towards potentially critical social evaluation in a real-world environment. Participants were 77 early adolescent girls (ages 11–13) oversampled for shy/fearful temperament. Results support the reliability of this in vivo attention task. Further, girls with more positive functional connectivity between the right amygdala and anterior PFC during both rejection and acceptance feedback attended more to potentially critical social evaluation during the attention task. Findings could suggest that dysfunction in prefrontal regulation of the amygdala's response to salient social feedback supports heightened sensitivity to socially evaluative threat during adolescence.